Decentralization of Mexico’s Agricultural Extension Services and the Ongoing Struggle to Alleviate Rural Poverty - José M. Uscanga; M. Craig Edwards (Journal of International Agricultural and Extension Education, 2016)
Atendencytodecentralizenationalagriculturalextensionsystemsaroundtheworldcaughtmanycountriesunpreparedtorespondeffectivelytotheneedsofitsruralpopulationunderprivatizedapproachestoextensiondelivery,especiallyinregardtopovertyalleviation.MyriadinternalandexternalfactorsledMexicotodismantleitsnationalagriculturalextensionsysteminthe1990s,andadoptamoreprivatizedorcontractor-drivenapproach.Asaresult,significantchangesoccurredinthewayextensionserviceswereofferedtothepublicafterthesystem’sdecentralizationbyMexico’sfederalgovernment,althoughsomesimilaritiesremained.Afteralmosttwodecadesofdecentralization,theeffectivenessofthecurrentsystemhasbeenquestionedregardingitsprovisionofservicestomarginalizedgroupswhorepresentthemostimpoverishedofMexico’scitizens.Thishistoricalnarrativeaimedtounderstandthephenomenonbyexploringthecausesofdecentralization,comparingextensionservicedeliverybeforeandafterdecentralization,includingitsoutcome,privatizationofextensionservices,andsuggestdirectionsforimprovementinthefuture
Keywords: agricultural extension; decentralization; Mexico; rural poverty